2017
DOI: 10.1111/jcpe.12811
|View full text |Cite
|
Sign up to set email alerts
|

Do different probing depths exhibit striking differences in microbial profiles?

Abstract: Aim: To perform a thorough characterization of the subgingival microbiota of shallow, moderate and deep sites in subjects with chronic periodontitis (ChP). Material and methods:Subgingival samples were collected from subjects with ChP (n = 3/category of probing depth: ≤3, 4-6 and ≥7 mm) and periodontal health (PH).Individual samples were submitted to 16S rDNA high-throughput sequencing and the analysis was made using mothur and R packages.Results: Nine subjects with ChP and seven with PH were included and 101 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 45 publications
5
51
3
Order By: Relevance
“…Second, our sampling strategy called for collection of four subgingival plaque samples (each harvested from the mesio-lingual surface of the most posterior tooth in each quadrant) which were subsequently pooled into a single sample/participant. Given the established association between PD and microbial profiles, 8,[35][36][37] the mesiolingual, rather than the commonly used mesio-buccal site was purposefully selected to avoid microbial sampling from shallower pockets due to gingival recession. Importantly, our data showed that the probing depths of the sampled sites were, on average, deeper than, but strongly positively correlated with, the whole mouth scores.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our sampling strategy called for collection of four subgingival plaque samples (each harvested from the mesio-lingual surface of the most posterior tooth in each quadrant) which were subsequently pooled into a single sample/participant. Given the established association between PD and microbial profiles, 8,[35][36][37] the mesiolingual, rather than the commonly used mesio-buccal site was purposefully selected to avoid microbial sampling from shallower pockets due to gingival recession. Importantly, our data showed that the probing depths of the sampled sites were, on average, deeper than, but strongly positively correlated with, the whole mouth scores.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, NGS has been widely used to analyze subgingival bacterial composition and to characterize compositional shifts between periodontal health and disease (Liu et al, 2012 ; Abusleme et al, 2013 ; Li et al, 2015 ; Park et al, 2015 ; Han et al, 2017 ). Some studies observed the striking differences between the microbiota of healthy sites (probing depth ≤ 3 mm) and diseased sites in ChP subjects (Ge et al, 2013 ; Pérez-Chaparro et al, 2018 ), as it is known that the composition of the subgingival microbiome varies according to probing depths possibly because of dissimilar ecological parameters such as oxygen tension (Loesche et al, 1983 ; Abusleme et al, 2013 ). However, there is scarce evidence on the shift of subgingival microbiome in individual tooth sites of both types of periodontitis during disease development.…”
Section: Introductionmentioning
confidence: 99%
“…7 Up to 15 taxa could be differentiated simultaneously using combinatorial labeling and the spectral imaging-FISH technique, whereas this number is still very limited compared with that of more than 200 taxa that have been detected in subgingival plaques. [8][9][10][11] The other barrier in the subgingival plaque structure study is in the mature subgingival plaque accessing, particularly for the surface layer. 12 Until now, tooth extraction is the only method to obtain undisturbed natural subgingival plaques, which is unrepeatable and could only be applied to a hopeless tooth.…”
Section: Introductionmentioning
confidence: 99%